1998
DOI: 10.1103/physrevb.58.11197
|View full text |Cite
|
Sign up to set email alerts
|

Observation of bound surface states in grain-boundary junctions of high-temperature superconductors

Abstract: We have performed a detailed study of the tunneling spectra of bicrystal grain boundary junctions (GBJs) fabricated from the high temperature superconductors (HTS) YBa2Cu3O 7−δ (YBCO), Bi2Sr2CaCu2O 8+δ (BSCCO), La1.85Sr0.15CuO4 (LSCO) and Nd1.85Ce0.15CuO4−y (NCCO). In all experiments the tunneling direction was along the CuO2 planes. With the exception of NCCO, for all materials a pronounced zero bias conductance peak (ZBCP) was observed which decreases with increasing temperature and disappears at the critica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
103
1

Year Published

1999
1999
2004
2004

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 129 publications
(114 citation statements)
references
References 34 publications
10
103
1
Order By: Relevance
“…In contrast, the I c (H) patterns of NCCOand PCCO-GBJs are close to a regular Fraunhofer diffraction pattern expected for an ideal Josephson junction [13]. Finally, the tunneling spectra measured for NCCO do not show any zero bias anomaly giving strong evidence for the absence of a sign change in the superconducting pair potential [5,18,21]. These experimental facts exclude both a d x 2 −y 2 -and d xy -symmetry of the OP for NCCO and PCCO.…”
mentioning
confidence: 68%
See 2 more Smart Citations
“…In contrast, the I c (H) patterns of NCCOand PCCO-GBJs are close to a regular Fraunhofer diffraction pattern expected for an ideal Josephson junction [13]. Finally, the tunneling spectra measured for NCCO do not show any zero bias anomaly giving strong evidence for the absence of a sign change in the superconducting pair potential [5,18,21]. These experimental facts exclude both a d x 2 −y 2 -and d xy -symmetry of the OP for NCCO and PCCO.…”
mentioning
confidence: 68%
“…However, there is no problem with the results of tunneling measurements. It has been shown that there is no qualitative difference in the tunneling spectra between NCCO and PCCO for 2 K< T < T c [5,18].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The hallmark of a pure d-wave OP in the tunneling spectra is the zero bias conductance peak (ZBCP) observed for tunneling along and near the nodal [110] direction [5][6][7][8][9][10][11] , reflecting the existence of surface Andreev bound states at the Fermi level [12][13][14][15][16] . In addition, U and V-shaped gaps can be seen, respectively, in the [100] and [001] directions 8, 11 , 15, 17, 18 .…”
Section: Introductionmentioning
confidence: 99%
“…In Chapter 4 we present a qualitative discussion of how a ZBCP may appear in voltage biased d|d junctions. This study was motivated by recent experiments [20,21]. In Chapter 5 we summarize the paper.…”
Section: Introductionmentioning
confidence: 99%